(untitled) (Journal of Partial Differential Equations, 2020)
The limiting absorption principle is used to solve the scattering problem of time harmonic acoustic waves by penetrable objects in Sobolev spaces. The method is based on integral representation of the solution using the Green's kernel of the Helmholtz equation.